Geospatial based soil loss rate and land degradation assessment in Debre Berhan Regio-Politan city, Upper Blue Nile Basin, Central Ethiopia - Yitea Seneshaw Getahun; Fikrey Tesfay; Alemnew Berhanu Kassegne; Alebachew Shumye Moges (Geomatics, Natural Hazards & Risk)
In Ethiopia’s central highlands, soil erosion and degradation are the most challenging and persistent issues, owing to their rough topography and human activities. Planning land use and managing natural resources, as well as agricultural output, depend on the evaluation of land degradation (LD). Thus, this study was carried out with the objective to quantify and evaluate soil loss rates, sediment yield (SY), and identify degradation hotspot areas in the Debre Berhan Regio-Politan City, Central Highlands of Ethiopia. The city has an area of 127191.7 ha. The Revised Universal Soil Loss Equation (RUSLE) model was applied to generate soil erosion severity map. An empirical equation based on topography was utilized to calculate sediment yield, in addition to the Analytical Hierarchy Process (AHP) method for evaluating land LD. The results showed that the city’s average annual estimated soil loss was 38.5 t ha−1 yr−1. Serious risks of soil loss are especially present in large portions of the city’s hilly eastern, northwest, and north peripheral areas. The city’s yearly average SY varies from 0–32 t ha−1 yr−1, with plain areas generally contributing 0 tons, while the hilly/barren areas contributing 32 tons. The LD severity class indicated that about 15197.65 ha (11.91%), 38018.49 ha (29.85%), 40287.86 ha (31.67%), 19869.97 ha (15.61%), and 13817.73 ha (10.96%) portion is categorized as very low, low, moderate, high, and very high, respectively. To prevent soil loss and LD and increase agricultural productivity, it is crucial to implement nature-based climate-smart agricultural practices and provide capacity-building training in line with the SDGs, Africa Agenda 2063, and national strategies and policies of the country.